2020
DOI: 10.1074/mcp.ra120.002082
|View full text |Cite
|
Sign up to set email alerts
|

The Mouse Heart Mitochondria N Terminome Provides Insights into ClpXP-Mediated Proteolysis

Abstract: The mammalian mitochondrial proteome consists of more than 1100 annotated proteins and their proteostasis is regulated by only a few ATP-dependent protease complexes. Technical advances in protein mass spectrometry allowed for detailed description of the mitoproteome from different species and tissues and their changes under specific conditions. However, protease-substrate relations within mitochondria are still poorly understood. Here, we combined Terminal Amine Isotope Labeling of Substrates (TAILS) N termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 68 publications
(81 reference statements)
1
36
0
Order By: Relevance
“…These potential ClpP substrates were assessed on the STRING web platform, revealing a strongly significant protein–protein interaction enrichment ( p < 1 × 10 −16 ). STRING generated a diagram of protein–protein interactions that highlights a prominent network of mitoribosomal components and molecular chaperones, as described [ 12 , 16 ]; in comparison, the assembly factors for iron–sulfur cluster biosynthesis and respiratory chain elements as well as mitochondrial enzymes played a minor role ( Figure S1 ). The detailed analysis of enrichments ( Table S2 ) also documented the previously reported increase in cytosolic innate immunity mediators [ 15 ], and a novel elevation in secreted collagen precursors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These potential ClpP substrates were assessed on the STRING web platform, revealing a strongly significant protein–protein interaction enrichment ( p < 1 × 10 −16 ). STRING generated a diagram of protein–protein interactions that highlights a prominent network of mitoribosomal components and molecular chaperones, as described [ 12 , 16 ]; in comparison, the assembly factors for iron–sulfur cluster biosynthesis and respiratory chain elements as well as mitochondrial enzymes played a minor role ( Figure S1 ). The detailed analysis of enrichments ( Table S2 ) also documented the previously reported increase in cytosolic innate immunity mediators [ 15 ], and a novel elevation in secreted collagen precursors.…”
Section: Resultsmentioning
confidence: 99%
“…A wider spectrum of targets was described for the mitochondrial matrix peptidase ClpP, which plays important roles during the unfolded protein response for mitochondria (UPR mt ) [ 8 , 9 ]. It depends on AAA+ ATPases such as ClpX for activation, substrate selection, and disaggregation, thus converting into a protease [ 10 , 11 , 12 ]. Two heptameric ClpP rings assemble with hexameric ClpX rings on either side into a barrel-shaped unfolding and degradation machine [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also shown that some core subunits (NDUFS1, NDUFV1 and NDUFV2) of the matrix-facing N module of complex I are selectively turned over by the ClpXP protease in the mitochondrial matrix [33][34] . In light of this, it will be important to reconcile how quality control proteases crosstalk with MDV formation and cargo incorporation, particularly since Clpp was identified as enriched in MDVs in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the direct role of ClpXP and LON in metabolic regulation is highly feasible yet understudied. Indeed, the proteomic analysis of ClpXP-deficient models and substrate screens reveals substantial changes in intramitochondrial metabolism and highlight several plausible substrates [103,106,110,112,116].…”
Section: Mitochondrial Oxphos Systemmentioning
confidence: 99%